Overweight and Obesity and Associated Factors among School-Aged Adolescents in Six Pacific Island Countries in Oceania - Pengpid, Supa (Int J Environ Res Public Health, 2015)
The aim of this study was to assess overweight and obesity and associated factors in school-going adolescents in six Pacific Island countries in Oceania. The sample included 10,424 school-going adolescents predominantly 13–16 years old from Fiji, Kiribati, Samoa, Solomon Islands, Tonga, and Vanuatu. Bivariate and multivariable analyses were conducted to assess the relationship between dietary behaviour, substance use, physical activity, psychosocial factors, social-familial influences, and overweight or obesity. The prevalence of overweight and obesity was determined based on self-reported height and weight and the international child body mass index standards. Results indicate a prevalence of overweight or obesity of 24.3% and obesity of 6.1% in the six countries, ranging in terms of overweight or obesity and obesity from 12.0% and 0.4% in Vanuatu to 58.7% and 21.1% in Tonga, respectively. In multivariable regression analysis, being female was associated with overweight, carbonated soft drink use with obesity, sedentary behaviour with overweight or obesity, suicidal ideation with overweight, having close friends and peer support with overweight and obesity, parental or guardian supervision with overweight, and parental or guardian bonding was associated with overweight or obesity. High prevalence rates of overweight and obesity were found and several factors identified which can help guide interventions.